Using the TAT to Assess the Relation Between Gender Identity and the Use of Defense Mechanisms. Issue 3 (4th May 2017) - Cramer, Phebe
ABSTRACT: The purpose of this study is to explore whether 2 different dimensions of personality, when assessed at an implicit level with the Thematic Apperception Test (TAT; Murray, 1943 ) will show a theoretically meaningful coherence not demonstrated when 1 is assessed at an implicit level and the other at an explicit level. Gender identity and defense mechanisms were assessed implicitly using the TAT. Gender identity was compared with a self-report measure of gender-related attributes assessed at the explicit level. The results showed a theoretically meaningful coherence when different dispositions were assessed at the same level, but a lack of agreement when similar dispositions were assessed at different levels. The study is based on a secondary analysis of data from 2 previously published papers (Cramer, 1998 ; Cramer & Westergren, 1999 ).